Associations of Environmental Features With Outdoor Physical Activity on Weekdays and Weekend Days: A Cross-Sectional Study Among Older People - Keskinen, Kirsi E.; Gao, Ying; Rantakokko, Merja; Rantanen, Taina; Portegijs, Erja (Frontiers in Public Health, 2020)
Background: Physical activity (PA) of higher intensity and longer duration mainly accumulates from older adults’ out-of-home activities. Outdoor PA is influenced by environmental features; however, the day-to-day variability of PA and its associations with environmental features have not been widely studied. This study focused on the associations of environmental features with accelerometer-measured PA in older people on weekdays and weekend days. Methods: The study population comprised 167 community-dwelling older people aged 75 to 90 years. Accelerometers were worn on seven consecutive days and a structured interview on physical functioning, health, and socioeconomic factors was administered. A geographic information system (GIS) was used to assess environmental features within a distance of 500 (number of land types, road network slope, intersection and residential densities) or 1 000 meters (habitat diversity within natural and green areas) from participants’ homes. Accelerometer-based PA (number of PA bouts > 10 minutes and minutes of moderate to vigorous physical activity (MVPA)) was analyzed for weekdays and weekend days separately. Associations between environmental features and PA were analyzed using linear regression models. Results: Participants accumulated on average 0.60 PA bouts and 34.2 MVPA minutes on weekdays and 0.50 PA bouts and 31.5 MVPA minutes on weekend days. Especially participants with low overall PA were less active at weekends. Habitat diversity in natural and green areas, intersection density, and residential density were positively associated with numbers of PA bouts and MVPA minutes on weekdays. Moreover, more diversity in natural and green areas was associated with more MVPA minutes on weekend days. A higher road network slope was negatively associated with the number of PA bouts throughout the week and with MVPA minutes on weekend days. Conclusions: Environmental features close to home, especially PA-supportive infrastructural features and services, were more strongly associated with weekday than weekend PA. This suggests that older people’s out-of-home activities, typically conducted on weekdays, are related to service use. However, greater diversity of natural areas close to home seemed to motivate older adults to engage in higher MVPA throughout the week.